Work Pay, Contractual Changes and Employee Attrition: Evidence from NHS Trainee Doctors - Marco Mello; Giuseppe Moscelli; Ioannis Laliotis; Melisa Sayli (Institute of Labor Economics (IZA), 2024)
Retention of skilled workers is critical for the delivery of public services in high-stakes environments such as hospital care. We study how contractual pay terms affect the retention of trainee doctors in the English NHS and the relationship between trainee doctors' attrition and hospital quality. Our setting is a nationwide reform that reduced unsocial working hours pay rates. Using a longitudinal sample and a novel linkage of administrative datasets, our quasi difference-in-difference strategy leverages the pre-reform exposure of each trainee doctor to unsocial working hours and suggests that the implementation of the new pay terms led to a 6.7% increase in the annual number of trainee doctors leaving the English NHS. As plausible mechanism, we show that the reform was detrimental to pay satisfaction and increased trainee doctors intentions to change job outside healthcare. By exploiting the effect of the reform, we also document a positive association between trainee doctors' attrition and hospital mortality.
Keywords: I11; J22; J41; J45; J81; C23; 330; job contracts; employee attrition; pay satisfaction; on-the-job training; doctors; hospitals; patient mortality